The End of Poverty: How We Can Make It Happen in Our Lifetime - Jeffrey D. Sachs (Great Britain Penguin Books, 2005)
Jeffrey Sachs draws on his remarkable 25 years' experience to offer a thrilling and inspiring vision of the keys to economic success in the world today. Marrying vivid storytelling with acute analysis, he sets the stage by drawing a conceptual map of the world economy and explains why, over the past 200 years, wealth and poverty have diverged and evolved across the planet, and why the poorest nations have been so markedly unable to escape the trap of poverty. Sachs tells the remarkable stories of his own work in Bolivia, Poland, Russia, India, China and Africa to bring readers with him to an understanding of the different problems countries face. In the end, readers will be left not with an understanding of how daunting the world's problems are, but how solvable they are - and why making the effort is both our moral duty and in our own interests.
Keywords: Economics; Nonfiction; Politics; Poverty; International relations; Sociology; Business; Global Citizenship (BIN1064-N)